Strategic Isolation of a Polyoxocation Mimicking Vanadium(V) Oxide Layered-Structure by Stacking of [H2V2O8]4− Anions Bridged by (1,4,7-Triazacyclononane)Co(III) Complexes - Sugiarto,; Kawamoto, Keisuke; Hayashi, Yoshihito (Frontiers in Chemistry, 2018)
An isolation of a vanadium(V) oxide cluster mimicking V2O5 layered structure was achieved formulated as [Co(tacn)4V4O12(OH)4]4+ (1) (tacn = 1,4,7-triazacyclononane). From the 51V NMR spectra of the reaction mixtures, we optimized the reaction condition in terms of a molar ratio of VO43− and [Co(tacn)(H2O)3]3+ as well as a pH value. Cluster 1 is stable in a wide range of pH values from 1.5 to 8.0, and the presence of multiple hydrogen bondings in the structure is a unique feature. In the X-ray analysis of cluster 1, the V⋯ V distances are classified into two groups of relatively shorter distances (2.978(1) Å) and longer interactions (3.554(1) Å), and it is a good model of the substructure of V2O5 bulk material. As far as we know, this is a first example of an isolation of mixed-metal cluster including a unit of V2O5 structure by a stack of two layers of [H2V2O8]4−, although cubic V4O4 cubane-type clusters are well known. The solid sample of compound 1-Cl and 1-Br shows reversible thermochromic behavior accompanied by crystal to amorphous transformation upon hydration-dehydration process.